Zr-Fe bimetallic atom catalyst, preparation method thereof and application of Zr-Fe bimetallic atom catalyst in wide-temperature zinc air battery
By introducing zirconium (Zr) into the Fe-N-C catalyst, the Zr-Fe bimetallic atomic catalyst was prepared, which solved the problem of narrow operating temperature range of the M-N-C catalyst, improved ORR activity and stability, and expanded its applicable temperature range.
Patent Information
- Application Number
- CN202411806159.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
AI Technical Summary
The existing transition metal-nitrogen-carbon (M-N-C) single-atom catalyst has a narrow operating temperature range, limiting its environmental applicability and versatility in other energy conversion and storage.
The Zr, Fe-co-doped carbon-based composite material was prepared as a bimetal atomic catalyst by introducing the pre-transition metal zirconium (Zr) into the Fe-N-C catalyst by non-contact chemical vapor deposition (CVD). The introduction of Zr regulates the spin state of the Fe center, optimizes the Fe-Nx coordination environment, and reduces the binding energy to the reaction intermediate.
The oxygen reduction reaction (ORR) activity and stability of Fe-N-C catalysts is significantly improved, its operating temperature range is expanded, and it shows better performance in applications in alkaline zinc air batteries.
Smart Images

Figure CN119627130A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst materials, and in particular to a Zr-Fe bimetallic atom catalyst and a preparation method thereof, and application thereof in a wide-temperature zinc-air battery. Background Art
[0002] Oxygen reduction reaction (ORR) is the key reaction in the discharge process of zinc-air batteries. It is true that noble metal alloys currently exhibit excellent ORR catalytic activity in alkaline, neutral and acidic electrolytes. However, the scarcity and high price of noble metals have greatly limited the further commercialization of zinc-air batteries.
[0003] Transition metal-nitrogen-carbon (MNC) single-atom catalysts have excellent ORR catalytic activity, high atom utilization, tunable electronic structure, highly exposed active sites and efficient O2 adsorption capacity, and are considered to be the most promising alternatives to precious metal-based catalysts. Among them, Fe-NC catalysts show the best ORR intrinsic catalytic activity. However, the operating temperature range of this ORR catalyst is relatively narrow, mostly limited to around room temperature (25 °C), which greatly hinders its environmental applicability and versatility in other energy conversion and storage.
[0004] In addition, the low ion transfer rate and electrolyte freezing at low temperatures lead to slow reaction kinetics of the Fe-NC catalyst ORR. At the same time, the ion transfer rate increases significantly at higher temperatures, exacerbating the corrosion of the anode zinc plate and the leaching of the active metal sites of the catalyst in the air cathode and carbon corrosion, which leads to a sharp reduction in battery life and reduces the reactivity and stability of the Fe-NC catalyst. Summary of the invention
[0005] In view of the shortcomings of the prior art mentioned above, the object of the present invention is to provide a Zr-Fe bimetallic atom catalyst and a preparation method thereof, and application in a wide temperature range zinc-air battery, so as to solve the problem that the existing transition metal-nitrogen-carbon (MNC) single atom catalyst has a narrow operating temperature range, which hinders its environmental applicability and versatility in other energy conversion and storage.
[0006] To achieve the above-mentioned purpose and other related purposes, the present invention provides a method for preparing a Zr-Fe bimetallic atomic catalyst, wherein a Fe-NC catalyst and ZrCl4 powder are placed in a heating zone of a tubular furnace in a non-contact manner, and reacted at 500~1200°C to obtain a Zr / Fe-NC catalyst, i.e., a Zr-Fe bimetallic atomic catalyst.
[0007] The present invention introduces the early transition metal zirconium (Zr) into the Fe-NC catalyst by non-contact chemical vapor deposition (CVD) to obtain a Zr, Fe co-doped carbon-based composite material. As a bimetallic atomic catalyst, the introduction of Zr can effectively regulate the spin state of the Fe center and optimize the Fe-NC x The coordination environment of Fe-NC is improved, which reduces its binding energy to the reaction intermediates and significantly improves the ORR activity and stability of Fe-NC catalysts. Compared with the existing Fe-NC, the prepared Zr-Fe bimetallic atom catalyst has a wider operating temperature range and has great performance advantages in the application of alkaline zinc-air batteries, which is conducive to improving the ORR activity and electrochemical stability of Fe-NC-based catalysts in a wide temperature range.
[0008] Preferably, the preparation method of the Fe-NC catalyst comprises: (1) Containing Zn 2 +, Fe 2+ The reaction solution of the ligand and the solvent is reacted at 40-100 °C to obtain FeZn-ZIFs; (2) Calcine FeZn-ZIFs under a protective atmosphere to obtain Fe-NC catalyst.
[0009] ZIF-8 is a porous crystalline material formed by the self-assembly of Zn (II) and 2-methylimidazole, and has adjustable pore size, highly stable structure and catalytic activity. The present invention uses ZIF-8 as a template and dopes Fe by condensation reflux method to obtain FeZn-ZIFs. During the synthesis process, not only the integrity of the porous carbon skeleton structure of ZIF-8 is retained, but also there are no Fe metal nanoparticles therein, and the Fe element exists in the composite material in the form of a single atom. In the preparation process of the Fe-NC catalyst, Zn is removed by high-temperature pyrolysis, leaving a porous structure that exposes more active sites and introduces oxygen-containing functional groups, which is beneficial to the electrocatalytic reaction.
[0010] Preferably, in step (2), the calcination temperature is 600-1200°C, the calcination time is 0.5-3 h, and the heating rate is 25-30°C min -1 .
[0011] Preferably, the preparation method of FeZn-ZIFs comprises: 2 +, Fe 2+ The reaction solution of , ligand and solvent is reacted at 40~100 °C to obtain FeZn-ZIFs.
[0012] More preferably, in the above-mentioned method for preparing FeZn-ZIFs, washing and drying steps are also included after the reaction.
[0013] More preferably, the washing step comprises: firstly washing by centrifugation with a methanol solution for 3 times, and then washing once with ethanol.
[0014] More preferably, the drying process adopts vacuum drying, and the vacuum drying temperature is 50-80° C. and the time is 12-48 hours.
[0015] Preferably, the ligand is 2-methylimidazole and the solvent is methanol.
[0016] Preferably, in step (1), Zn 2 + and Fe 2+ Disperse in a solvent to obtain a solution A, disperse the ligand in a solvent to obtain a solution B, quickly mix the solution A and the solution B, and react under stirring conditions.
[0017] Preferably, the reaction temperature is 50-80° C., the reaction time is 20-36 h, and the stirring rate is 300-600 rpm.
[0018] Preferably, the Fe-NC catalyst is first placed in the heating zone of the tubular furnace, and the ZrCl4 powder is placed in the non-heating zone of the tubular furnace. After the temperature is raised to 600-800°C, the ZrCl4 powder is transferred from the non-heating zone to the heating zone.
[0019] Preferably, protective gas is first introduced into the tubular furnace to exhaust the air in the tube, and the temperature is controlled to rise at 20-25° C. / min.
[0020] Preferably, the mass ratio of the Fe-NC catalyst to the ZrCl4 powder is (5-20):1.
[0021] The present invention also provides a Zr-Fe bimetallic atom catalyst prepared by the above preparation method.
[0022] The present invention also provides an application of the Zr-Fe bimetallic atom catalyst in a wide-temperature zinc-air battery.
[0023] As described above, the present invention has the following beneficial effects: (1) The early transition metal zirconium (Zr) was introduced into the Fe-NC catalyst by non-contact chemical vapor deposition (CVD) to obtain a Zr, Fe co-doped carbon-based composite material. As a bimetallic atom catalyst, the introduction of Zr can effectively regulate the spin state of the Fe center and optimize the Fe-NC x The coordination environment of Fe-NC catalysts is improved, which reduces the binding energy of Fe-NC catalysts to the reaction intermediates and significantly improves the ORR activity and stability of Fe-NC catalysts. The preparation conditions are relatively mild and the parameters are controllable. (2) Compared with precious metal-based catalysts, the production cost is significantly reduced; (3) Improve the ORR activity and stability of the catalyst compared to traditional Fe-NC catalysts; (4) It has a wider operating temperature range and better performance in the application of flexible zinc-air batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Shown is the SEM image of the precursor FeZn-ZIFs prepared in Example 1.
[0025] Figure 2 Shown are SEM images of the single atom catalyst Fe-NC (a) and the bimetallic atom catalyst Zr / Fe-NC (b) prepared in Example 1.
[0026] Figure 3 Shown are the TEM image (a), ring selected area electron diffraction SAED image (b) and EDX mapping (c) of the Zr / Fe-NC catalyst prepared in Example 1.
[0027] Figure 4 Shown is the XRD pattern of the precursor FeZn-ZIFs prepared in Example 1.
[0028] Figure 5 Shown are the XRD patterns of the Fe-NC and Zr / Fe-NC catalysts prepared in Example 1.
[0029] Figure 6 Shown are the linear voltammetric sweep (LSV) curves of Zr / Fe-NC catalysts, commercial Pt / C and Fe-NC catalysts obtained with different ZrCl4 feed ratios in 0.1 M KOH electrolyte.
[0030] Figure 7 Shown are the H2O2 selectivity curves at different potentials calculated for Zr / Fe-NC catalysts obtained with different ZrCl4 feed ratios, commercial Pt / C and Fe-NC catalysts in 0.1 M KOH electrolyte.
[0031] Figure 8 Shown is the open circuit voltage of the Zr / Fe-NC catalyst prepared in Example 1 applied to a quasi-solid-state flexible zinc-air battery at -40°C.
[0032] Fig. 9 Shown is the open circuit voltage of the Zr / Fe-NC catalyst prepared in Example 1 applied to a quasi-solid-state flexible zinc-air battery at 60°C. DETAILED DESCRIPTION
[0033] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0034] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.
[0035] In addition, it should be understood that one or more method steps mentioned in the present invention do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between these explicitly mentioned steps, unless otherwise specified; it should also be understood that the combination connection relationship between one or more devices / apparatuses mentioned in the present invention does not exclude the existence of other devices / apparatuses before or after the combination device / apparatus or the insertion of other devices / apparatuses between these explicitly mentioned two devices / apparatuses, unless otherwise specified. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.
[0036] Example 1 The present invention provides a method for preparing a Zr-Fe bimetallic atom catalyst, comprising the following steps: Step (1): Preparation of FeZn-ZIFs precursor: 3.39 g Zn(NO3)2·6H2O and 80 mg Fe(NO3)2·9H2O were dissolved in 500 mL methanol, labeled as solution A; 3.94 g 2-methylimidazole was dissolved in 500 mL methanol, labeled as solution B. Then, solutions A and B were quickly mixed and stirred at 60 °C for 24 h, with a stirring rate of 400 rpm. After the reaction was completed, the sample was washed three times with methanol and once with ethanol, and then vacuum dried at 60 °C.
[0037] Step (2): Preparation of single-atom catalyst Fe-NC: Weigh 200 mg of FeZn-ZIFs powder and place it in a crucible, put it into a tube furnace, introduce nitrogen for 30 min, heat it to 1000 °C at a rate of 25 °C / min, keep it at 1000 °C for 1 h, and then cool it naturally to room temperature under nitrogen protection to obtain a sample single-atom catalyst Fe-NC; Step (3): Preparation of bimetallic atom catalyst Zr / Fe-NC: Weigh 10 mg of the prepared Fe-NC powder and 100 mg of ZrCl4 powder respectively and place them in two different crucibles, then place the crucible containing ZrCl4 powder in the front non-heating zone of the tube furnace, and place the crucible containing Fe-NC powder in the heating zone of the tube furnace behind the ZrCl4 powder crucible. Pass nitrogen for 30 min, and heat to 750 °C at a rate of 25 °C / min. Then push the crucible containing ZrCl4 powder into the heating zone, keep it at 750 °C for 1 h, and then cool it naturally to room temperature under nitrogen protection. Then, the sample Zr / Fe-NC 10:1 is obtained, which is the Zr-Fe bimetallic atom catalyst.
[0038] The material obtained in this example was characterized, and the results were as follows: Figure 1 a is a SEM image of the precursor FeZn-ZIFs obtained in Example 1. It can be seen from the figure that the prepared FeZn-ZIFs material presents a regular dodecahedron morphology, and its particle size is about 30 nm.
[0039] Figure 2 a and Figure 2 b is the SEM image of the single atom catalyst Fe-NC and the bimetallic atom catalyst Zr / Fe-NC obtained in Example 1, showing that Fe-NC and Zr / Fe-NC present a regular dodecahedral structure, and the particle size is about 30 nm.
[0040] Figure 3 a is a TEM image of the bimetallic atom catalyst Zr / Fe-NC obtained in Example 1. Figure 3 It can be seen in a that there are no metal nanoclusters on the carbon substrate of the Zr / Fe-NC composite material. Figure 3 b is the ring selected area electron diffraction (SAED), which shows that the composite material has an amorphous structure, and it is speculated that the Zr and Fe elements exist in the composite material in the form of single atoms. Figure 3 c Energy dispersive X-ray element (EDX) image, indicating the uniform distribution of Zr, Fe, C, N, and O elements in the Zr / Fe-NC composites.
[0041] Figure 4 is the precursor FeZn-ZIFs obtained in Example 1, Figure 5The XRD patterns of single-atom catalyst Fe-NC and dual-metal site single-atom catalyst Zr / Fe-NC are shown in Figure 2. It can be seen from the XRD pattern that FeZn-ZIFs has high crystallinity and has similar peak shape and peak position to standard ZIF-8, indicating that the introduction of Fe element does not affect the structure of the prepared ZIFs; no diffraction peaks related to metal Fe were observed in Fe-NC, and there were no diffraction peaks related to Fe and Zr in Zr / Fe-NC, and only 3 carbon characteristic peaks existed, indicating that there were no Fe and Zr metal nanoparticles in the composite material.
[0042] The prepared composite material was subjected to a rotating ring disk electrode test, and the test results are as follows: Figure 6 shown. Figure 6 The LSV curves show that the catalysts exhibit excellent ORR activity in O2-saturated 0.1 M KOH electrolyte, with Zr / Fe-NC (Zr / Fe-NC 10:1) having an onset potential (Eonset) of 1.06 V and a half-wave potential (Eonset) of 0.93 V. 1 / 2 ), which is better than Fe-NC (Eonset = 1.00 V, E 1 / 2 = 0.87 V), Zr / Fe-NC 5:1 (Eonset = 1.02 V, E 1 / 2 = 0.91 V), Zr / Fe-NC 20:1 (Eonset = 1.00 V, E 1 / 2 = 0.89 V), and even commercial Pt / C (Eonset = 0.99 V, E 1 / 2 = 0.85 V) catalyst. In addition, Figure 7 It shows that the HO2 − The yields were 0.05 ~ 2.26%, which is comparable to commercial Pt / C catalysts (1.55 ~ 1.88%) and much lower than Fe-NC (0.09 ~ 6.8%), Zr / Fe-NC 5:1 (0.07 ~ 3.81%), and Zr / Fe-NC 20:1 (0.16 ~ 9.12%) catalysts. This result indicates that Zr / Fe-NC can catalyze ORR at 4e − The path is carried out, which is beneficial to improving the energy utilization rate of O2.
[0043] The application performance in quasi-solid-state flexible zinc-air batteries is shown by Figure 8It can be seen that the battery using Zr / Fe-NC maintains a higher open circuit voltage of 1.486 V and is more stable over a long period of time, while the battery using Fe-NC has an open circuit voltage of 1.332 V, which can be attributed to the slow and unstable reaction kinetics caused by the low temperature environment, the reduced electrolyte ion conductivity or the presence of freezing. Fig. 9 The results show that the battery using Zr / Fe-NC still maintains a relatively high open circuit voltage of 1.494 V and slightly increases, while the battery using Fe-NC has an open circuit voltage of 1.377 V, which is due to the improvement of catalytic activity and ion transfer rate under high temperature environment. This result shows that Zr / Fe-NC can work stably for a long time in a wider temperature range, which improves the environmental applicability and versatility of non-precious metal-based catalysts in energy conversion and storage.
[0044] Example 2 The present invention provides a method for preparing a Zr-Fe bimetallic atom catalyst, comprising the following steps: Step (1): Preparation of FeZn-ZIFs precursor: 3.39 g Zn(NO3)2·6H2O and 80 mg Fe(NO3)2·9H2O were dissolved in 500 mL methanol, labeled as solution A; 3.94 g 2-methylimidazole was dissolved in 500 mL methanol, labeled as solution B. Then, solutions A and B were quickly mixed and stirred at 60 °C for 24 h, with a stirring rate of 400 rpm. After the reaction was completed, the sample was washed three times with methanol and once with ethanol, and then vacuum dried at 60 °C.
[0045] Step (2): Preparation of single-atom catalyst Fe-NC: Weigh 200 mg of FeZn-ZIFs powder and place it in a crucible. Place it in a tube furnace and introduce nitrogen for 30 min. Raise the temperature to 1000 °C at a rate of 25 °C / min. Keep at 1000 °C for 1 h and then cool naturally to room temperature under nitrogen protection to obtain a sample single-atom catalyst Fe-NC.
[0046] Step (3): Preparation of bimetallic single atom catalyst Zr / Fe-NC: Weigh 10 mg of the prepared Fe-NC powder and 50 mg of ZrCl4 powder respectively and place them in two different crucibles, then place the crucible containing ZrCl4 powder in the front non-heating zone of the tube furnace, and place the crucible containing Fe-NC powder in the heating zone of the tube furnace behind the ZrCl4 powder crucible. Pass nitrogen for 30 min, raise the temperature to 750 °C at a rate of 25 °C / min, then push the crucible containing ZrCl4 powder into the heating zone, keep it at 750 °C for 1 h, and then naturally cool it to room temperature under nitrogen protection to obtain the sample Zr / Fe-NC 5:1.
[0047] The samples in the embodiment were selected for characterization and analysis, and the test results are as follows: The LSV curve of the rotating ring disk electrode test found that Zr / Fe-NC 5:1 (Eonset = 1.02 V, E 1 / 2 = 0.91 V), indicating that it has good ORR activity. In addition, the HO2 − The yield is 0.07 ~ 3.81%, which can catalyze ORR at 4e − The path is carried out, which is beneficial to improving the energy utilization rate of O2.
[0048] Example 3 The present invention provides a method for preparing a Zr-Fe bimetallic atom catalyst, comprising the following steps: Step (1): Preparation of FeZn-ZIFs precursor: 3.39 g Zn(NO3)2·6H2O and 80 mg Fe(NO3)2·9H2O were dissolved in 500 mL methanol, labeled as solution A; 3.94 g 2-methylimidazole was dissolved in 500 mL methanol, labeled as solution B. Then, solutions A and B were quickly mixed and stirred at 60 °C for 24 h, with a stirring rate of 400 rpm. After the reaction was completed, the sample was washed three times with methanol and once with ethanol, and then vacuum dried at 60 °C.
[0049] Step (2): Preparation of single-atom catalyst Fe-NC: Weigh 200 mg of FeZn-ZIFs powder and place it in a crucible. Place it in a tube furnace and introduce nitrogen for 30 min. Raise the temperature to 1000 °C at a rate of 25 °C / min. Keep at 1000 °C for 1 h and then cool naturally to room temperature under nitrogen protection to obtain a sample single-atom catalyst Fe-NC.
[0050] Step (3): Preparation of bimetallic single atom catalyst Zr / Fe-NC: Weigh 10 mg of the prepared Fe-NC powder and 200 mg of ZrCl4 powder respectively and place them in two different crucibles, then place the crucible containing ZrCl4 powder in the front non-heating zone of the tube furnace, and place the crucible containing Fe-NC powder in the heating zone of the tube furnace behind the ZrCl4 powder crucible. Pass nitrogen for 30 min, raise the temperature to 750 °C at a rate of 25 °C / min, then push the crucible containing ZrCl4 powder into the heating zone, keep it at 750 °C for 1 h, and then naturally cool it to room temperature under nitrogen protection to obtain the sample Zr / Fe-NC 20:1.
[0051] The samples in the embodiment were selected for characterization and analysis, and the test results are as follows: The LSV curve of the rotating ring disk electrode test found that Zr / Fe-NC 20:1 (Eonset = 1.00 V, E 1 / 2 = 0.89 V), indicating that it has good ORR activity. − The yield is 0.16 ~ 9.12%, which can catalyze ORR at 4e − The path is carried out, which is beneficial to improving the energy utilization rate of O2.
[0052] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical ideas disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing a Zr-Fe bimetallic atom catalyst, characterized in that: The Fe-NC catalyst and ZrCl4 powder are placed in a heating zone of a tube furnace in a non-contact manner and reacted at 500-1200°C to obtain a Zr / Fe-NC catalyst, that is, a Zr-Fe bimetallic atom catalyst.
2. The preparation method according to claim 1, characterized in that: The preparation method of the Fe-NC catalyst comprises: 2 +、Fe 2+ The reaction solution of the ligand and the solvent is reacted at 40-100 °C to obtain FeZn-ZIFs; (2) the FeZn-ZIFs are calcined under a protective atmosphere to obtain a Fe-NC catalyst.
3. The preparation method according to claim 2, characterized in that: In step (2), the calcination temperature is 600-1200°C, the calcination time is 0.5-3 h, and the heating rate is 25-30°C min −1 .
4. The preparation method according to claim 2, characterized in that: In step (1), the ligand is 2-methylimidazole and the solvent is methanol.
5. The preparation method according to claim 2, characterized in that: In step (1), Zn 2 + and Fe 2+ Disperse in a solvent to obtain solution A, disperse the ligand in a solvent to obtain solution B, quickly mix solution A and solution B, and react under stirring conditions. The reaction temperature is 50-80°C, the reaction time is 20-36 h, and the stirring rate is 300-600 rpm.
6. The preparation method according to claim 1, characterized in that: First, the Fe-NC catalyst is placed in the heating zone of the tube furnace, and the ZrCl4 powder is placed in the non-heating zone of the tube furnace. After the temperature is raised to 600~800℃, the ZrCl4 powder is transferred from the non-heating zone to the heating zone.
7. The preparation method according to claim 6, characterized in that: First, introduce protective gas into the tubular furnace to exhaust the air in the tube, and control the temperature rise to 20~25℃ / min.
8. The preparation method according to claim 1, characterized in that: The mass ratio of the Fe-NC catalyst to the ZrCl4 powder is (5~20):
1.
9. A Zr-Fe bimetallic atom catalyst prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the Zr-Fe bimetallic atom catalyst as claimed in claim 9 in a wide temperature zinc-air battery.